2006
DOI: 10.1007/s00018-005-5498-0
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin in human lymphoid tissues

Abstract: When nephrin, the protein product of NPHS1, was cloned, it was proposed to be specific for the kidney glomerular podocytes. Recently, however, new reports have emerged verifying additional nephrin expression sites, particularly the insulin-producing beta cells of the pancreas, as well as the central nervous system. In this study, we demonstrate nephrin expression in lymphoid tissues, specifically the tonsil, adenoid and lymph node. Nephrin mRNA expression levels were 4-fold higher in tonsils and adenoids than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Consistent with previous reports, we also identified the 160-kDa nephrin band in extrarenal organs: heart, spleen, pancreas, and brain (Supplemental Figure 1E). 7,34,35 The exclusive presence of the 180-kD band in the kidney lysate has been described previously. 35 Because DOX does not cross the blood-brain barrier, GFP and nephrin expressions did not different between mice with and without induction.…”
Section: Murine Model Of Inducible Nephrin Knockdownmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous reports, we also identified the 160-kDa nephrin band in extrarenal organs: heart, spleen, pancreas, and brain (Supplemental Figure 1E). 7,34,35 The exclusive presence of the 180-kD band in the kidney lysate has been described previously. 35 Because DOX does not cross the blood-brain barrier, GFP and nephrin expressions did not different between mice with and without induction.…”
Section: Murine Model Of Inducible Nephrin Knockdownmentioning
confidence: 99%
“…7,34,35 The exclusive presence of the 180-kD band in the kidney lysate has been described previously. 35 Because DOX does not cross the blood-brain barrier, GFP and nephrin expressions did not different between mice with and without induction. Histologic features of the myocardium did not appear to be different between sh3703 and Luci.1309 mice (Supplemental Figure 1F).…”
Section: Murine Model Of Inducible Nephrin Knockdownmentioning
confidence: 99%
“…In contrast, cadherin-11 expression increases during the formation of multinucleated syncytia, and it promotes the morphological and functional differentiation of human CTB cells (Getsios & MacCalman 2003). The expression of nephrin has been found in the kidney, pancreas, brain, and lymphoid tissues (Putaala et al 2001, Astrom et al 2006. Verma et al (2006) have observed that mutation or deletion of nephrin protein in the slit diaphragm in the kidney leads to a defect in podocyte foot process morphogenesis, and that proteinuria is the clinical symptom.…”
Section: Discussionmentioning
confidence: 99%
“…It becomes more and more evident that, outside the nervous system, glutamate signalling is utilized not only by podocytes but also by other cells, such as lymphocytes, testis cells and pancreatic β cells, all of them requiring precise modulation of specific functions. Not surprisingly, nephrin expression has been selectively found in the very same locations 52–55, and it will be interesting to investigate its molecular interactions also in these systems.…”
Section: Discussionmentioning
confidence: 99%